PENINGKATAN HASIL BELAJAR SISWA MELALUI MEDIA POP UP PADA MATERI IPA SIKLUS AIR DI KELAS V SEKOLAH DASAR - Yulia Indra Sari Dewi; Nandang Budiman; Novi Ayudyaningtias (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background of this research is the low learning outcomes of students in class V water cycle science material in an elementary school in Bandung city which is still below the KKM average due to students' lack of understanding of the material being taught because the material is abstract. This study aims to describe the use of Pop Up media to increase student learning outcomes in class V water cycle science material at an elementary school in the city of Bandung in the 2022/2023 Academic Year. The research method used is collaborative classroom action research with 3 cycles. The research subjects were fifth grade students at an elementary school in the city of Bandung. Data collection was carried out through interviews, observation, and tests. The results showed that the use of Pop Up media in improving student learning outcomes in science material the water cycle was considered effective in the learning process of students actively observing and using Pop Up media to assist them in learning, there was an increase in student learning outcomes through Pop Up media as evidenced by the average mastery of classical learning in each cycle increased from cycle I to cycle II of 16.67%, there was an increase from 83.33% to 100% and strengthening was carried out in cycle III with the average acquisition of classical learning mastery reaching a KKM value of 100%. which indicates that all students are complete in learning. Therefore, Pop Up media can be used by teachers to improve student learning outcomes in the water cycle science material.